Efektivitas Proyek Alat Peraga Teori Atom 3D Berbasis STEM Terhadap Hasil Belajar Siswa - Ros Amanda, Ade; Kurniasih, Dedeh; Kurniati, Tuti (Chemistry Education Practice, 2024)
The insufficient engagement of students in the learning process is linked to the utilization of teaching models and tools that fail to encourage direct involvement. Hence, there is a need to devise a learning framework that emphasizes active student participation. One potential strategy is project-based learning, integrating science, technology, engineering, and mathematics (STEM). This research aims to determine the effectiveness of the STEM-based 3D atomic theory teaching aids project on student learning outcomes. This research is a quantitative research with a pre-experimental design method type one group pretest-posttest with a sample of 30 class X SMAIT Al-Fityan Kubu Raya students taken using a purposive sampling technique. The data collection tools used were pretest and posttest and observation sheets. Testing the normality of the distribution of each pretest and posttest group using the SPSS 26.0 for Windows test. The results of the research show that there is an increase in student learning outcomes from 18% to 82% with an effect size value of 5.03 obtaining the Strong Effect category. This research shows that STEM-based 3D atomic theory teaching aid project learning is effective in improving student learning outcomes.